Interface Engineering for All‐Inorganic CsPbI2Br Perovskite Solar Cells with Efficiency over 14 - Yan, Lei; Xue, Qifan; Liu, Meiyue; Zhu, Zonglong; Tian, Jingjing; Li, Zhenchao; Chen, Zhen; Chen, Ziming; Yan, He; Yip, Hin‐Lap; Cao, Yong (Advanced materials (Weinheim), 2018)
In this work, a SnO2/ZnO bilayered electron transporting layer (ETL) aimed to achieve low energy loss and large open‐circuit voltage (Voc) for high‐efficiency all‐inorganic CsPbI2Br perovskite solar cells (PVSCs) is introduced. The high‐quality CsPbI2Br film with regular crystal grains and full coverage can be realized on the SnO2/ZnO surface. The higher‐lying conduction band minimum of ZnO facilitates desirable cascade energy level alignment between the perovskite and SnO2/ZnO bilayered ETL with superior electron extraction capability, resulting in a suppressed interfacial trap‐assisted recombination with lower charge recombination rate and greater charge extraction efficiency. The as‐optimized all‐inorganic PVSC delivers a high Voc of 1.23 V and power conversion efficiency (PCE) of 14.6%, which is one of the best efficiencies reported for the Cs‐based all‐inorganic PVSCs to date. More importantly, decent thermal stability with only 20% PCE loss is demonstrated for the SnO2/ZnO‐based CsPbI2Br PVSCs after being heated at 85 °C for 300 h. These findings provide important interface design insights that will be crucial to further improve the efficiency of all‐inorganic PVSCs in the future. The open‐circuit voltage (Voc) and power conversion efficiency (PCE) of all‐inorganic perovskite solar cells (PVSCs) can be simultaneously enhanced by incorporating SnO2/ZnO bilayer as electron transporting layer (ETL). The favorable matching of cascade energy band between CsPbI2Br and SnO2/ZnO can effectively reduce charge recombination loss, resulting in highly efficient CsPbI2Br PVSCs with Voc and PCE up to 1.23 V and 14.6%, respectively.